Pengaruh Minat Menjadi Guru dan Prestasi Belajar Terhadap Kompetensi Pedagogik Mahasiswa Calon Guru - Novita Nurul Hidayah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
This research aims to analyze the influence of interest in becoming a teacher on the pedagogical competence of students, examine the impact of academic achievement on the pedagogical competence of students, and investigate the combined effects of interest and academic achievement on students' pedagogical competence. The research employs a quantitative method with a sample of 110 students from the 2016 cohort of the Teacher Education program at the State Islamic University Maulana Malik Ibrahim Malang. Data collection involves the distribution of questionnaires and documentation. The obtained data undergo validity and reliability testing, classical assumption testing, and multiple regression analysis. Based on the results of the multiple regression analysis, it is found that: (1) interest in becoming a teacher significantly influences the pedagogical competence of students at the Teacher Education program of Madrasah Ibtidaiyah; (2) academic achievement significantly affects the pedagogical competence of students in the Teacher Education program of Madrasah Ibtidaiyah; and (3) interest in becoming a teacher and academic achievement jointly influence the pedagogical competence of students in the Teacher Education program of Madrasah Ibtidaiyah. Additionally, the coefficient of determination, or R square, suggests that there are still other factors not covered in the study that may influence the pedagogical competence of students in Madrasah Ibtidaiyah Teacher Education.